1985
DOI: 10.1108/eb007982
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Residential Valuer in the House?

Abstract: This paper briefly examines the nature of residential valuations, questions the professional vigour with which such instructions are handled and raises a number of fundamental points that residential valuers need to be able to answer in the near future, if not to‐day. It concludes with the view that a statistical approach may be necessary in the future but will only be acceptable if based on accurate base data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Hager and Lord (1985) posited that the range of acceptance for property valuation inaccuracy should be about 5% more or less of the average value of the subject property. Similarly, Mackmin (1985) suggested that valuation estimates produced by valuers would be acceptable if they were within ± 5% range of the property value. Furthermore, Hutchinson et al (1996) argued that a valuation estimate within 5 to 10% range is acceptable, only when it is above 10% that the estimate can be subjected to contention.…”
Section: Property Valuation Accuracymentioning
confidence: 99%
“…Hager and Lord (1985) posited that the range of acceptance for property valuation inaccuracy should be about 5% more or less of the average value of the subject property. Similarly, Mackmin (1985) suggested that valuation estimates produced by valuers would be acceptable if they were within ± 5% range of the property value. Furthermore, Hutchinson et al (1996) argued that a valuation estimate within 5 to 10% range is acceptable, only when it is above 10% that the estimate can be subjected to contention.…”
Section: Property Valuation Accuracymentioning
confidence: 99%
“…In addition to accounting for constant quality among lot sizes, sale prices for vacant residential land in Hamilton are particularly 'noisy' . For example, error is introduced into sale prices because the price people pay for property is often ill-advised (Mackmin, 1985). Furthermore, Pollakowski warns that land registry data often contain non-arm's-length transactions in which reported prices are significantly below market levels because of a relationship between buyer and seller (Pollakowski, 1995, p. 380).…”
Section: Data and Processingmentioning
confidence: 99%
“…However, one of the main issues to arise from the research into market participants was to question whether valuers do in fact interpret the market in terms of buyer behaviour. Mackmin (1985) suggests that valuers traditionally categorise variables into two broad categories, those that are "internal" and those that are "external" to the property. In contrast to the internal factors of a property, which are relatively easy to measure in the valuation process, the external factors are difficult to specify and measure.…”
Section: Valuation Of Residential Propertymentioning
confidence: 99%